Safety and effectiveness of reduced-port laparoscopic sleeve gastrectomy in Asian morbidly obese patients - Yeshong Park; Young Suk Park; Sangjun Lee; So Hyun Kang; Eunju Lee; Sang-Hoon Ahn; Yun-Suhk Suh; Do Joong Park; Hyung-Ho Kim (Scientific Reports, 2021)
Abstract Laparoscopic sleeve gastrectomy is the most frequently performed surgical intervention in patients with morbid obesity. Single-port sleeve gastrectomy (SPSG) and reduced-port sleeve gastrectomy (RPSG) are increasingly reported in the literature. This study compared the short-term outcomes of SPSG, RPSG, and conventional laparoscopic sleeve gastrectomy (CLSG). This is a single-center retrospective study of 238 morbidly obese patients, of whom 148 (62.2%) patients completed follow-up one year after surgery. Propensity score matching was performed on factors influencing the choice of approach, and fifty patients from the SPSG + RPSG and CLSG groups were successfully matched. The groups were comparable in postoperative weight loss, morbidity, pain, and resolution of obesity-related comorbidities. The percentage of excess weight loss after one year was 90.0% in the SPSG + RPSG group and 75.2% in the CLSG group (P < 0.001). Complication rates showed no significant difference. The CLSG group was superior in dyslipidemia remission (17 [37.0%] vs. 28 [63.6%], P = 0.018) in the total cohort; however, this difference disappeared after matching. Our results suggest that single-port and reduced-port approaches could be alternative choices for selected patients. As our study was limited by its retrospective nature and potential selection bias, further studies are necessary to set standardized guidelines for SPSG.